DPRD Supervision of the Implementation of New Renewable Energy Policies From the Perspective of Good Governance - Kholik Idris; Edi Pranoto (Universitas Muhammadiyah Palu, 2025)
The adoption of Renewable Energy Policies (EBT) is a vital step towards ensuring energy sustainability in Indonesia, given the declining reliance on fossil fuels and the associated environmental impacts. Effective monitoring is crucial for the successful implementation of EBT policies at the regional level. The Regional People's Representative Council (DPRD) plays a key role in overseeing these policies. This research aims to assess DPRD's oversight function regarding the implementation of EBT policies through the lens of Good Governance, emphasizing transparency, accountability, participation, and responsibility. Effective oversight is expected to drive the achievement of sustainable EBT policy outcomes that ultimately benefit the community.